2020
DOI: 10.1155/2020/5490468
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity ofFicus deltoideaExtract on Oral Cancer: An In Vivo Study

Abstract: Background. The aim of this study is to evaluate the chemopreventive and chemotherapeutic activities of Ficus deltoidea (FD) in an animal model induced for oral cancer using 4-nitroquinoline-1-oxide (4NQO). Methods. Male Sprague-Dawley (SD) rats were randomized into six groups (n = 7 per group): Group 1 (untreated group); Group 2 (control cancer group) received 4NQO only for 8 weeks in their drinking water; Groups 3 and 4 (chemopreventive) received 4NQO for 8 weeks and were simultaneously treated with FD extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Notably, the average weight of the Perio group increased week on week over the whole experiment; however, there was no difference compared with the Control group, which is in accordance with the results of other studies (18,19). Regarding the groups exposed to 4NQO, there was ~10% less weight gain from baseline to the final week compared with that in the control groups, with a particular slight drop in the final four weeks, which is also in line with the results of other studies (15,(30)(31)(32). Significant differences were observed in the last weeks between the Perio group and the groups exposed to 4NQO.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the average weight of the Perio group increased week on week over the whole experiment; however, there was no difference compared with the Control group, which is in accordance with the results of other studies (18,19). Regarding the groups exposed to 4NQO, there was ~10% less weight gain from baseline to the final week compared with that in the control groups, with a particular slight drop in the final four weeks, which is also in line with the results of other studies (15,(30)(31)(32). Significant differences were observed in the last weeks between the Perio group and the groups exposed to 4NQO.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of these compounds is bene cial for treating dyslipidemia, diabetes, heart disease, cancer, and infertility cases such as PCOS. The antihypertensive [11], chemopreventive, and chemotherapeutic [12] activities of F. deltoidea have indeed been reported in animal studies. F. deltoidea also improved depressive behavior in rats [13].…”
Section: Introductionmentioning
confidence: 76%
“…10,11,36 Previous studies have shown that an extract from plants in the Ficus genus exhibits anti-proliferative effects via modulating cell cycle arrest, apoptosis, and angiogenesis. [37][38][39] For example, the F. carica extract caused S phase arrest and increased the levels of p21 in breast cancer MDA-MB-231 cells. 37 Hanafi et al reported that F. deltoidea extract inhibits the growth of prostate cancer cells via apoptosis.…”
Section: Discussionmentioning
confidence: 99%